Physical Exercise Activity In Elderly Gymnastics And Its Effect On Sleep Quality: A Literature Review - Savitri, Richa; Fahdi, Faisal Kholid; Fradianto, Ikbal (ProNers, 2024)
Background: Aging is a natural process accompanied by a decline in physical, mental, and social functions. One common health issue in older adults is sleep disturbances, which significantly affect their quality of life. Non-pharmacological interventions, such as physical exercise, are effective in addressing sleep issues without adverse side effects.Objective: This literature review aimed to explore the impact of physical exercise, specifically gymnastics, on sleep quality in older adults.Methods: A literature review was conducted using the PICOT framework. Articles were sourced from Google Scholar, Portal Garuda, and ResearchGate, using keywords related to elderly, gymnastics, and sleep quality in both English and Indonesian. Inclusion criteria included articles published between 2015 and 2020, full-text availability, and relevance to the topic. Seven articles meeting the inclusion criteria were analyzed.Results: Various types of physical exercise, including yoga, ergonomic gymnastics, Tai Chi, and low-impact aerobic exercise, were found to significantly improve sleep quality in older adults. These exercises enhance relaxation, improve blood circulation, and reduce stress, resulting in better sleep patterns. For example, yoga was associated with reduced muscle tension and improved oxygen flow to the brain, while ergonomic gymnastics and Tai Chi promoted relaxation and stable blood pressure. Aerobic exercises were found to alleviate stress and increase positive emotions, contributing to improved sleep quality.Conclusion: Physical exercise plays a vital role in enhancing sleep quality among older adults. Structured and regular activities such as yoga, Tai Chi, ergonomic gymnastics, and aerobic exercise are effective non-pharmacological interventions to address sleep disturbances. Promoting these activities can improve the overall well-being and quality of life of older adults.